ANALISIS PERSEPSI KINERJA PELAYANAN SEKOLAH BINA BHAKTI KABUPATEN KUBU RAYA - Juliahir Barata; Udin Rinaldi (STIE 'INDONESIA' Pontianak, 2018)
Survey research was conducted at Sekolah Bina Bhakti Kabupaten Kubu Raya with descriptive method. Variables consist of service performance that is limited to 5 (five) dimensions, namely reliability; responsiveness; guarantee; empathy; and manifestations. The main priority dimension of research variables is considered important to note, because the services undertaken by institutions have not been in accordance with the wishes of stakeholders. Therefore, the institution should do business so that user satisfaction can be achieved. Based on cartesian diagram mapping, the variables dimension is the ability of the officer to respond quickly to complaints, ease / speed in service, attention of officer to the complaint, ease in fulfilling the desire of service user. While low priority is considered important in the variable dimension of the flexibility of payment time in case of delay.